2018
DOI: 10.48550/arxiv.1811.09678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Speech recognition with quaternion neural networks

Titouan Parcollet,
Mirco Ravanelli,
Mohamed Morchid
et al.

Abstract: Neural network architectures are at the core of powerful automatic speech recognition systems (ASR). However, while recent researches focus on novel model architectures, the acoustic input features remain almost unchanged. Traditional ASR systems rely on multidimensional acoustic features such as the Mel filter bank energies alongside with the first, and second order derivatives to characterize time-frames that compose the signal sequence. Considering that these components describe three different views of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…They found that Q achieved faster convergence on the training loss as well as higher classification accuracy on the test set compared to R. Gaudet and Maida [10] made a similar comparison with image classification on the CIFAR-10 and CIFAR-100 datasets and image segmentation on the KITTI Road Segmentation dataset [9], but this time with Q having a quarter of the number of parameters as R. They reported that on both tasks, quaternion models gave higher accuracy than real and complex networks while having a lower parameter count. Similar advantages for quaternion neural networks over real networks were also found by Parcollet et al [29] for speech recognition.…”
Section: Quaternionssupporting
confidence: 78%
See 1 more Smart Citation
“…They found that Q achieved faster convergence on the training loss as well as higher classification accuracy on the test set compared to R. Gaudet and Maida [10] made a similar comparison with image classification on the CIFAR-10 and CIFAR-100 datasets and image segmentation on the KITTI Road Segmentation dataset [9], but this time with Q having a quarter of the number of parameters as R. They reported that on both tasks, quaternion models gave higher accuracy than real and complex networks while having a lower parameter count. Similar advantages for quaternion neural networks over real networks were also found by Parcollet et al [29] for speech recognition.…”
Section: Quaternionssupporting
confidence: 78%
“…Using higher-dimensional data embeddings, such as complex numbers or quaternions, has been successfully shown to reduce model parameters while maintaining accuracy [39,38,10,27]. Quaternions are a 4-dimensional extension to the complex numbers introduced by the mathematician William Rowan Hamilton in 1843 [27], and quaternion neural networks have been built for a variety of ML tasks [43,29,10,28,32,4]. Converting a real model to quaternion can lead to a 75% reduction in model parameters (which is explained in more detail in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Tay et al explored the use of quaternion networks for lightweight and efficient neural natural language processing in [43]. Parcollet et al investigated the use of quaternion-valued convolutional and recurrent neural networks on speech recognition in [44]. Parcollet et al studied the use of quaternion neural networks for theme identification of telephone conversations in [45].…”
Section: Previous Work On Quaternion Neural Networkmentioning
confidence: 99%
“…Specifically, a quaternion number, containing one real part and three imaginary parts, and the corresponding quaternion-based neural networks [39][40][41][42] are expected to enhance the performance on processing of data with more degrees of freedom than the conventional real-number and complex-number systems. There have been various proposals about quaternion-based neural networks in ML techniques and applications in computer science, such as the quaternion convolutional neural network (qCNN) [38,43,44], quaternion recurrent neural network [45], quaternion generative adversarial networks [46], quaternion-valued variational autoencoder [47], quaternion graph neural networks [48], quaternion capsule networks [49] and quaternion neural networks for the speech recognitions [50]. However, the ML-related applications of the quaternion-based neural networks on solving problems in physics are still limited, especially in the topological phase detections, even though the quaternion-related concepts have been applied in some fields in physics [51][52][53].…”
Section: Introductionmentioning
confidence: 99%